Dynamics Of Migration In Islamic View - Sigit Danuansyah Madiawan S. (Islamic Studies Journal for Social Transformation, 2021)
Migration is an issue that has long been occurring in this part of the world, but not a few circles claim that it is an action that threatens domestic conditions. Islam itself has been practicing since prophetic times known as Hijrah. This paper will discuss how the Islamic view of migration often states that it can be a threat to the security and stability of the country in this increasingly modern era. This paper uses a qualitative descriptive method with the findings that America, which is used as a mecca for a superpower, has a different view from migration, which can be a serious threat to the country, while Islam has another view, namely that migration or hijrah is a necessity if the situation not possible to settle in the country of origin.